2003
DOI: 10.1373/49.3.450
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the FibroTest Biochemical Markers Score in Assessing Liver Fibrosis in Hepatitis C Patients

Abstract: Background: Determining the stage of fibrosis by liver biopsy is important in managing patients with hepatitis C virus infection. We investigated the predictive value of the proprietary FibroTest score to accurately identify significant fibrosis in Australian hepatitis C patients. Methods: Serum obtained from 125 confirmed hepatitis C patients before antiviral therapy was analyzed for haptoglobin, α2-macroglobulin, apolipoprotein A1, bilirubin, and γ-glutamyltransferase activity, and the FibroTe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
133
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(140 citation statements)
references
References 16 publications
2
133
0
5
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17][18][19][20] These noninvasive tools have a rather good positive predictive value for the diagnosis of moderate or significant fibrosis. [8][9][10][11][12][13][14][15][16][17][18][19][20] They are also simple, inexpensive, and easily reproducible. None of the available biomarkers actually meets these criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15][16][17][18][19][20] These noninvasive tools have a rather good positive predictive value for the diagnosis of moderate or significant fibrosis. [8][9][10][11][12][13][14][15][16][17][18][19][20] They are also simple, inexpensive, and easily reproducible. None of the available biomarkers actually meets these criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Liver biopsy (LB) is however limited by its invasive nature [1][2][3] ; poor acceptance, especially when repeated measures are required; availability and cost, particularly in non-Western countries; intra-and interobserver variability 4,5 ; and sampling errors, which produce approximately 24% of false negatives for cirrhosis. 6,7 Consequently, noninvasive tests to assess hepatic fibrosis have been developed, such the AST-to-platelet ratio index (APRI), 8 the Forns test, 9 and FibroTest (Biopredictive SAS, Paris, France), [10][11][12][13][14][15][16] which combine several biochemical parameters. More recently, transient elastography (FibroScan, Echosens, Paris, France)-a morphological method that measures liver stiffness-has been evaluated.…”
mentioning
confidence: 99%
“…The score has been validated in other HCV cohorts, but not all studies achieved the same results. [65][66][67] The paper by Rossi et al 67 found that the FibroTest could not reliably predict the presence or absence of fibrosis in 125 patients with HCV, using local assays and the original authors' computer program to calculate the FibroTest score. However, a recent metaanalysis found that FibroTest is effective in the evaluation of hepatic fibrosis in chronic HCV and chronic hepatitis B virus (HBV), alcoholic liver disease, and nonalcoholic fatty liver disease (NAFLD); and the authors concluded that FibroTest is, in fact, an effective alternative to liver biopsy.…”
Section: Fibrotest and Fibrosurementioning
confidence: 99%
“…With biopsy as the standard of reference, the diagnostic value of FT for a diagnosis of advanced fibrosis (bridging fibrosis), as estimated by the area under the ROC curve (AUROC), is 0.73-0.86 (8 ). AUROC values inside the range of other studies have been reported, but the usefulness of FT compared with biopsy was not established (17 ). Discordance between FT and biopsy may be related to biopsy failure due mainly to sampling errors and to false-positive and false-negative FT results related to Gilbert syndrome, hemolysis, or acute inflammation (8,18 ).…”
mentioning
confidence: 93%